ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP DOLAN COFFEE - Naafika Rachma Rozani; Hwihanus Hwihanus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The research that will be shown to simplify the financial operational system and management of coffee raw materials uses a java-based information system. This research method uses the library study method. A literature study is carried out by researching and looking for some of the problems that often arise among coffee shops with the same goal but done by surfing the internet and visiting several sites in the coffee shop. Making this application can also facilitate the performance of coffeshops such as data input and raw material management because so far coffeeshop performance has been done manually and the impact is large on input errors and inaccuracies.